# 小明思考

Just a software engineer
posts - 124, comments - 36, trackbacks - 0, articles - 0
BlogJava :: 首页 :: 新随笔 :: 联系 :: 聚合  :: 管理
Problem

Given a string s1, we may represent it as a binary tree by partitioning it to two non-empty substrings recursively.
Below is one possible representation of s1 = "great":
great
/    \
gr    eat
/ \    /  \
g   r  e   at
/ \
a   t
To scramble the string, we may choose any non-leaf node and swap its two children.
For example, if we choose the node "gr" and swap its two children, it produces a scrambled string "rgeat".
rgeat
/    \
rg    eat
/ \    /  \
r   g  e   at
/ \
a   t
We say that "rgeat" is a scrambled string of "great".
Similarly, if we continue to swap the children of nodes "eat" and "at", it produces a scrambled string "rgtae".
rgtae
/    \
rg    tae
/ \    /  \
r   g  ta  e
/ \
t   a
We say that "rgtae" is a scrambled string of "great".
Given two strings s1 and s2 of the same length, determine if s2 is a scrambled string of s1.

public boolean isScramble(String s1, String s2) {
int l1 = s1.length();
int l2 = s2.length();
if(l1!=l2){
return false;
}
if(l1==0){
return true;
}

char[] c1 = s1.toCharArray();
char[] c2 = s2.toCharArray();
if(l1==1){
return c1[0]==c2[0];
}
Arrays.sort(c1);
Arrays.sort(c2);
for(int i=0;i<l1;++i){
if(c1[i]!=c2[i]){
return false;
}
}

boolean result = false;
for(int i=1;i<l1 && !result;++i){
String s11 = s1.substring(0,i);
String s12 = s1.substring(i);
String s21 = s2.substring(0,i);
String s22 = s2.substring(i);
result = isScramble(s11,s21) && isScramble(s12,s22);
if(!result){
String s31 = s2.substring(0,l1-i);
String s32 = s2.substring(l1-i);
result = isScramble(s11,s32) && isScramble(s12,s31);
}
}

return result;
}

result[k][i][j]表示s1[i...i+k]是否可以由s2[j...j+k]变化得来。

public class Solution {
public boolean isScramble(String s1, String s2) {
int len = s1.length();
if(len!=s2.length()){
return false;
}
if(len==0){
return true;
}

char[] c1 = s1.toCharArray();
char[] c2 = s2.toCharArray();

boolean[][][] result = new boolean[len][len][len];
for(int i=0;i<len;++i){
for(int j=0;j<len;++j){
result[0][i][j] = (c1[i]==c2[j]);
}
}

for(int k=2;k<=len;++k){
for(int i=len-k;i>=0;--i){
for(int j=len-k;j>=0;--j){
boolean r = false;
for(int m=1;m<k && !r;++m){
r = (result[m-1][i][j] && result[k-m-1][i+m][j+m]) || (result[m-1][i][j+k-m] && result[k-m-1][i+m][j]);
}
result[k-1][i][j] = r;
}
}
}

return result[len-1][0][0];
}
}

 只有注册用户登录后才能发表评论。 网站导航: 相关文章: